Comparative Study of Spatial Prediction Models for Estimating PM2.5 Concentration Level in Urban Areas - Vargas-Campos I.R. (2021)
Acknowledgment. The authors gratefully acknowledge financial support by Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica (Fondecyt) -Mundial Bank (Grant: 50-2018-FONDECYT-BM-IADT-MU).